Proceedings of the 2003 International Conference on Machine Learning and Cybernetics (IEEE Cat. No.03EX693)
DOI: 10.1109/wsc.2003.1261483
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale network simulations with GTNetS

Abstract: When designing a network simulation environment intended specifically for modeling large-scale topologies, a number of issues must be addressed by the simulator designer. Memory requirements for network simulation engines can grow quadratically with the size of the simulated topology and can easily exceed available memory on modern workstations. The number of outstanding simulation events grows linearly with the number of packets in flight being modeled, and can lead to performance bottlenecks when managing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…By Fujimoto et al [7], ns-2, PDNS [26] and GTNeTS [27] simulation tools were compared and it was indicated that ns-2 works quicker.…”
Section: Comparison Of Network Simulation Toolsmentioning
confidence: 99%
“…By Fujimoto et al [7], ns-2, PDNS [26] and GTNeTS [27] simulation tools were compared and it was indicated that ns-2 works quicker.…”
Section: Comparison Of Network Simulation Toolsmentioning
confidence: 99%
“…One of the most common approaches is to use integrated simulation environments such as ns-2 [4], ns-3 [5], OMNeT, NCTUns, GTNets [6]. The main advantage is the availability of precise and well tested models of communication protocols.…”
Section: Simulation Environment Selectionmentioning
confidence: 99%
“…The design of GTNetS matches closely the design of actual network protocol stacks and other network elements. Further, GTNetS was designed from the beginning to run a distributed environment, leading to better scalability Cheng et al (2006); Riley (2003); Zhang & Riley (2004).…”
Section: Gtnetsmentioning
confidence: 99%